2016
DOI: 10.1186/s12866-016-0675-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective hybrid coating containing silver, copper and zinc cations effective against human immunodeficiency virus and other enveloped viruses

Abstract: BackgroundHealthcare-acquired infections by pathogenic microorganisms including viruses represent significant health concern worldwide. Next to direct transmission from person-to-person also indirect transmission from contaminated surfaces is well documented and important route of infections. Here, we tested antiviral properties of hybrid coating containing silver, copper and zinc cations that was previously shown to be effective against pathogenic bacteria including methicillin-resistant Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 71 publications
(72 reference statements)
0
88
1
1
Order By: Relevance
“…This study did not investigate the effects of humidity as it has been shown that humidity does not impact the e cacy of copper's virucidal activity [Hodek et al, 2016]. Additionally, a study investigating the effect of humidity on In uenza A stability found that relative humidity had no signi cant impact on survivability [Kormuth et al, 2018].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This study did not investigate the effects of humidity as it has been shown that humidity does not impact the e cacy of copper's virucidal activity [Hodek et al, 2016]. Additionally, a study investigating the effect of humidity on In uenza A stability found that relative humidity had no signi cant impact on survivability [Kormuth et al, 2018].…”
Section: Discussionmentioning
confidence: 98%
“…Since In uenza A is an enveloped virus that is fairly prone to environmental stresses, it can be reasonably assumed that relative humidity will only impact the drying time for many viruses. However, if the evaporation rate of the virus is linked to the e cacy of the disinfectant (as with ethanol [Boyce, 2018] or silver surfaces [Hodek et al, 2016]), drying should be controlled to achieve a roughly standard drying time. When using 'ambient' humidity, it should still be recorded as the levels can change, with seasonal uctuations ranging from 15-48% in one study [Ramos et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, zinc plays other crucial roles including cell division, production of proteins and enhancing the functioning of the immune system. 16 Low intakes of zinc by the male respondents means that they were more predisposed to zinc deficiency, which is characterised by impaired immune function and loss of appetite. These symptoms can be fatal for male HIV-seropositive persons because loss of appetitive leads to under-nutrition and impaired immune function can increase their susceptibility to opportunistic infections such as tuberculosis, which can cause death.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms can be fatal for male HIV-seropositive persons because loss of appetitive leads to under-nutrition and impaired immune function can increase their susceptibility to opportunistic infections such as tuberculosis, which can cause death. 16 Finally, zinc deficiency amongst HIV-seropositive persons can worsen the severity of HIV infection.…”
Section: Discussionmentioning
confidence: 99%